Dialogic Pedagogy: Education for Social Justice (A Book Review of Pedagogy of the Oppressed by Paulo Freire) - Sharma, Pradip (Bon Voyage, 2025)
This book review examines Paulo Freire’s Pedagogy of the Oppressed, highlighting his transformative pedagogical concepts such as co-learning, dialogics, and cultural synthesis, fostering critical consciousness. Freire’s model of humanizing literacy seeks to restore learners’ dignity, creativity and autonomy. The review highlights the relevance of Freire’s educational insights, which empower individuals by freeing them from ‘intellectual tutelage’ and fostering critical consciousness. Doing so, it reveals his critique of the traditional banking model of education, which sustains intellectual domination, underscoring his new pedagogical insight of collaborative learning for fostering self-awakening among learners, that transcends class and gender divide. Reconsidering a stratified global society, the study, after a close reading, foregrounds Freire’s take on dialogics and cultural inclusion as a part of liberating humanity from the ideological incarceration of the oppressor. It also showcases the critique of the political structures that cultivate docile citizens, disseminating oppressor’s ideology through literacy policy that forbids their critical consciousness. Finally, the review affirms the ongoing relevance of Freire’s work in resisting dehumanizing literacy policies and promoting emancipatory education in modern contexts.